(untitled) (Research in Agriculture Livestock and Fisheries, 2026)
The occurrence of cutaneous infections in ruminants poses a significant threat to animal welfare and public health, particularly given the rise in antimicrobial resistance (AMR). In this study bacteria from skin wound infections of cattle, goats, and sheep were isolated and identified with their antibiogram profiles. A total of 100 clinical samples (cattle, n = 60; goats, n = 20; sheep, n = 20) were collected from various skin lesions of target animals in Dhaka, Bangladesh. Conventional cultural, morphological, and biochemical techniques were used to identify bacterial pathogens. Antimicrobial susceptibility testing was performed against nine commonly used antibiotics using the Kirby–Bauer disc diffusion method. Staphylococcus spp. was the most predominant isolate (51%), followed by Bacillus spp. (18%), Dermatophilus spp. (11%), and Streptococcus spp. (8%). Species-specific analysis revealed that Staphylococcus was most prevalent in cattle (53.33%), goats (50%), and sheep (45%). Maximum resistance was observed against β-lactam antibiotics. Conversely, the isolates demonstrated high susceptibility to fluoroquinolones (ciprofloxacin) and aminoglycosides (gentamicin). These findings underscore the high prevalence of multidrug-resistant (MDR) bacteria in ruminant skin wounds and emphasize the need for routine sensitivity testing to guide effective therapeutic interventions and combat the growing global health crisis of antimicrobial resistance. Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 41-51